Benzylic Alcohol Oxidation using Copper Oxide/ZincOxide/Zirconia Nanocomposite Catalysts. Issue 7 (17th February 2023) - Mokhtar, Mohamed; Panja, Subir; Alshehri, Abdulmohsen; Halawani, Wael; Maiti, Debabrata
Abstract: Herein, we have developed a nanocomposite catalyst for organic transformation. The catalysts are synthesized based on CuO/ZnO/ZrO2 materials through the coprecipitation method followed by calcination in air at 500 °C for 5 h. The physicochemical characterization using TGA, XRD, SEM and N2 ‐physisorption at −196 °C was carried out for all the prepared catalysts. Nanocomposite catalyst with Cu/Zn=1 : 1 showed the smallest particle size and largest surface area among all the other investigated catalysts. Under ideal reaction conditions, this new heterogenous catalyst has demonstrated its excellent efficacy for the oxidation of benzylic alcohol and can be successfully used in up to three catalytic cycles with little loss of catalytic activity. Abstract : CuO/ZnO/ZrO2 catalysts were tested for the oxidation reaction for benzylic alcohol derivatives. The catalysts showed superior catalytic efficiency under neat reaction condition.